2017
DOI: 10.1111/eos.12391
|View full text |Cite
|
Sign up to set email alerts
|

Genetic study of non‐syndromic tooth agenesis through the screening of paired box 9, msh homeobox 1, axin 2, and Wnt family member 10A genes: a case‐series

Abstract: study of non-syndromic tooth agenesis through the screening of paired box 9, msh homeobox 1, axin 2, and Wnt family member 10A genes: a case-series. Eur J Oral Sci 2018; 126: 24-32. © 2017 Eur J Oral Sci Non-syndromic tooth agenesis (NSTA) is the most common developmental anomaly in humans. Several studies have been conducted on dental agenesis and numerous genes have been identified. However, the pathogenic mechanisms responsible for NSTA are not clearly understood. We studied a group of 28 patients with spor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 42 publications
1
8
0
Order By: Relevance
“…In the past few years, much progress has been made in the identification of the developmental basis of odontogenesis and the genes involved in TA. [6][7][8][9][10][11][12] In fact, genetic polymorphisms in many genes, including MSX1 (msh homeobox 1), 20 PAX9 (paired box 9), 20 FGF3 (fibroblast growth factor 3), 7 FGF10 (fibroblast growth factor 10), 7 FGFR2 (fibroblast growth factor receptor 2), 7 FGFR1 (fibroblast growth factor receptor 1), 21 BMP2 (bone morphogenetic protein 2), 6 BMP4 (bone morphogenetic protein 4), 10,12 TGF 1 (transforming growth factor beta 1), 11 TGF 3 (transforming growth factor beta 3), 10 IRF6 (interferon regulatory factor 6), 9 MMP1 (matrix metalloproteinase 1), 22 MMP20 (matrix metalloproteinase 20), 22 MMP9 (matrix metalloproteinase 9), 10 MMP13 (matrix metalloproteinase 13), 10 and AXIN2 (axin-related protein 2) 20 have been associated with non-syndromic TA. However, to the best of our knowledge, this is the first study evaluating genetic ESR2 and tooth agenesis Marañón-Vásquez et al…”
Section: Discussionmentioning
confidence: 99%
“…In the past few years, much progress has been made in the identification of the developmental basis of odontogenesis and the genes involved in TA. [6][7][8][9][10][11][12] In fact, genetic polymorphisms in many genes, including MSX1 (msh homeobox 1), 20 PAX9 (paired box 9), 20 FGF3 (fibroblast growth factor 3), 7 FGF10 (fibroblast growth factor 10), 7 FGFR2 (fibroblast growth factor receptor 2), 7 FGFR1 (fibroblast growth factor receptor 1), 21 BMP2 (bone morphogenetic protein 2), 6 BMP4 (bone morphogenetic protein 4), 10,12 TGF 1 (transforming growth factor beta 1), 11 TGF 3 (transforming growth factor beta 3), 10 IRF6 (interferon regulatory factor 6), 9 MMP1 (matrix metalloproteinase 1), 22 MMP20 (matrix metalloproteinase 20), 22 MMP9 (matrix metalloproteinase 9), 10 MMP13 (matrix metalloproteinase 13), 10 and AXIN2 (axin-related protein 2) 20 have been associated with non-syndromic TA. However, to the best of our knowledge, this is the first study evaluating genetic ESR2 and tooth agenesis Marañón-Vásquez et al…”
Section: Discussionmentioning
confidence: 99%
“…Mutation of genes affects the sequence of genes in many ways. Recent studies have shown that genes such as PAX9, AXIN2, EDA, SPRY2, TGFA, SPRY4, WNT10A, FGF3, FGF10, FGFR2, and BMP4, are expressed in the odontogenesis process (13). PAX9, MSX1, AXIN2, and EDA are most commonly identified as non-syndromic hypodontia-related genes (14).…”
Section: Prevalence By Type Of Teethmentioning
confidence: 99%
“…9 It has been suggested that isolated tooth agenesis can result from mutations in MSX1 , PAX9 , WNT10A , AXIN2 , EDA , KDF1 , and SMOC2 genes in autosomal and X-linked traits. 10 - 14 Transcription factor genes MSX1 and PAX9 were the first identified genes responsible for tooth agenesis. 15 …”
Section: Introductionmentioning
confidence: 99%